Altered Intestinal Production of Volatile Fatty Acids in Dogs Triggered by Lactulose and Psyllium Treatment - Máté Mackei; Rebeka Talabér; Linda Müller; Ágnes Sterczer; Hedvig Fébel; Zsuzsanna Neogrády; Gábor Mátis (Veterinary Sciences, 2022)
The intestinal microbiome of dogs can be influenced by a number of factors such as non-starch polysaccharides as well as some non-digestible oligo- and disaccharides. These molecules are only decomposed by intestinal anaerobic microbial fermentation, resulting in the formation of volatile fatty acids (VFAs), which play a central role in maintaining the balance of the intestinal flora and affecting the health status of the host organism. In the present study, the effects of lactulose and psyllium husk (Plantago ovata) were investigated regarding their influence on concentrations of various VFAs produced by the canine intestinal microbiome. Thirty dogs were kept on a standard diet for 15 days, during which time half of the animals received oral lactulose once a day, while the other group was given a psyllium-supplemented diet (in 0.67 and in 0.2 g/kg body weight concentrations, respectively). On days 0, 5, 10 and 15 of the experiment, feces were sampled from the rectum, and the concentration of each VFA was determined by GC-MS (gas chromatography–mass spectrometry). Lactulose administration caused a significant increase in the total VFA concentration of the feces on days 10 and 15 of the experiment (p = 0.035 and p < 0.001, respectively); however, in the case of psyllium supplementation, the concentration of VFAs showed a significant elevation only on day 15 (p = 0.003). Concentrations of acetate and propionate increased significantly on days 5, 10 and 15 after lactulose treatment (p = 0.044, p = 0.048 and p < 0.001, respectively). Following psyllium administration, intestinal acetate, propionate and n-butyrate production were stimulated on day 15, as indicated by the fecal VFA levels (p = 0.002, p = 0.035 and p = 0.02, respectively). It can be concluded that both lactulose and psyllium are suitable for enhancing the synthesis of VFAs in the intestines of dogs. Increased acetate and propionate concentrations were observed following the administration of both supplements; however, elevated n-butyrate production was found only after psyllium treatment, suggesting that the applied prebiotics may exert slightly different effects in the hindgut of dogs. These findings can be also of great importance regarding the treatment and management of patients suffering from intestinal disorders as well as hepatic encephalopathy due to portosystemic shunt.